Changes of PTKP, PPh, PPN and PPnBM: its linkages on DJP East Java II - Mienati Somya Lasmana; Reni Eka Isyatir Rodhiyah (Asian Journal of Accounting Research, 2018)
The purpose of this paper is to know the relevance between the changes in non-taxable income with the receipt of Income Tax Article 21, Income Tax Article 25/29, the receipt of value added tax and the receipt of luxury sales tax r (PPnBM).Changes in non-taxable income have potentially reduced the receipt of Income Tax Article 21, Income Tax Article 25/29 of individual taxpayers, otherwise it increased value added tax and luxury sales tax receipts. This study used the descriptive qualitative approach, by conducting a simple case study based on actual data. Data analysis technique used is descriptive statistics and comparison analysis. Research conducted at the Kantor Wilayah Direktorat Jenderal Pajak Jawa Timur II.The results show that the changes of non-taxable income in 2013 and 2015 did not affect the receipt of Income Tax Article 21 but the growth is slowed, while the receipt of Income Tax Article 25/29 increased.Value added tax and luxury sales tax receipts, increasing every year, slowed down in 2013, but increased higher in 2015.